Can't Touch This Digital Approaches to Materiality in Cultural Heritage - Palladino, Chiara; Bodard, Gabriel (Ubiquity Press, 2023)
What are the implications of digital representation on intellectual property and ownership of cultural heritage? Are aspirations to preservation and accessibility in the digital space reconcilable with cultural sensitivities, colonized history, and cultural appropriation? This volume brings together different perspectives from academics and practitioners of Cultural Heritage, to address current debates in the digitization and other computational study of cultural artifacts. From the tension between the materiality of cultural heritage objects and the intangible character of digital models, we explore larger issues in intellectual property, collection management, pedagogical practice, inclusion and accessibility, and the role of digital methods in decolonization and restitution debates. The contributions include perspectives from a wide range of disciplines, addressing these questions within the study of the material culture of Africa, Europe, Asia, Oceania, and the Americas.